1998
DOI: 10.1128/jcm.36.2.552-556.1998
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of an Endemic Methicillin-Resistant Staphylococcus aureus Population in an Australian Hospital from 1967 to 1996

Abstract: The evolution over 30 years of a population of methicillin-resistant Staphylococcus aureus (MRSA) from a tertiary referral hospital was studied by phylogenetic analysis ofSmaI-generated restriction fragment length polymorphisms (RFLPs). The results suggest that a new clone of MRSA appeared at the hospital in the early 1980s, which, although usually retaining its ancestral phage-type, developed four different RFLP pulsotypes in the next 16 years. This finding indicates that multiple RFLP patterns in MRSA do not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(11 citation statements)
references
References 22 publications
1
10
0
Order By: Relevance
“…21,22 Detailed genetic analysis of MRSA strains from diverse parts of the world has revealed that transfer of SCCmec from a MRSA strain to a MSSA strain has occurred only a few times, and therefore the worldwide emergence of MRSA has resulted from dissemination of only a few clonal types rather than frequent de novo introduction of new MRSA clones. [21][22][23][24][25][26][27][28] These findings suggest that virtually all patients with MRSA infection or colonization have acquired their MRSA strain from an external source, and therefore control efforts must, in large part, focus on preventing transmission in addition to control of antimicrobial use. 22,26 Transmission of MRSA within and between healthcare facilities has been well documented using molecular typing techniques, such as pulsed-field gel electrophoresis (PFGE).…”
Section: Mrsamentioning
confidence: 99%
See 2 more Smart Citations
“…21,22 Detailed genetic analysis of MRSA strains from diverse parts of the world has revealed that transfer of SCCmec from a MRSA strain to a MSSA strain has occurred only a few times, and therefore the worldwide emergence of MRSA has resulted from dissemination of only a few clonal types rather than frequent de novo introduction of new MRSA clones. [21][22][23][24][25][26][27][28] These findings suggest that virtually all patients with MRSA infection or colonization have acquired their MRSA strain from an external source, and therefore control efforts must, in large part, focus on preventing transmission in addition to control of antimicrobial use. 22,26 Transmission of MRSA within and between healthcare facilities has been well documented using molecular typing techniques, such as pulsed-field gel electrophoresis (PFGE).…”
Section: Mrsamentioning
confidence: 99%
“…[21][22][23][24][25][26][27][28] These findings suggest that virtually all patients with MRSA infection or colonization have acquired their MRSA strain from an external source, and therefore control efforts must, in large part, focus on preventing transmission in addition to control of antimicrobial use. 22,26 Transmission of MRSA within and between healthcare facilities has been well documented using molecular typing techniques, such as pulsed-field gel electrophoresis (PFGE). Outbreaks involving clonal spread within single facilities have been frequently reported.…”
Section: Mrsamentioning
confidence: 99%
See 1 more Smart Citation
“…67,68 Successful control strategies for MRSA require infection control measures in addition to changes in antimicrobial usage. [69][70][71] The contribution of control strategies that involve changes in antimicrobial use, relative to that of infection control, is subject to debate, 72,73 but infection control practices must play a central role in successful MRSA control programs. 71,73 A recent discussion of the successful Dutch program appears to corroborate the conclusion that infection control has been the decisive element in MRSA control and that this has resulted in a much lower prevalence of MRSA in Dutch hospitals in comparison to those in most other European countries.…”
Section: Comparison To Methicillin Resistant Staphylococcus Aureusmentioning
confidence: 99%
“…Recently, methods of direct analysis of the bacterial genome, such as pulsed-field gel electrophoresis (PFGE), ribotyping (1,4,20), and random amplified polymorphic DNA analysis (21,29), have been used as alternative methods in the epidemiology of S. aureus infections. In particular, PFGE based on analysis of the whole genome by restriction endonuclease digestion has been shown to be a useful method for investigating the source, transmission, and spread of nosocomial infections and, more particularly, for epidemiologic typing and determination of the genetic relatedness of methicillin-resistant S. aureus strains (5,6,7,10,11,16). Also, PFGE has proven valuable in epidemiological studies of methicillin-resistant S. aureus found in horses (22,23) and dogs (19) in veterinary medicine.…”
mentioning
confidence: 99%